2012
DOI: 10.1177/0731684411435727
|View full text |Cite
|
Sign up to set email alerts
|

Micro-structural, thermal, and mechanical properties of injection-molded glass fiber/nanoclay/polypropylene composites

Abstract: Hybrid composites of PP/NC/GF were prepared by extrusion and injection molding. Molded specimens were analyzed by XRD, SEM, and TEM, together with characterization of thermal and mechanical properties. XRD results revealed that the interaction between NC particles and the PP matrix results in intercalation of the polymer chains, which increases the clay interlayer distance. TEM results revealed NC particle intercalation. TGA results showed that the incorporation of clay into the GF composite improves the therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…The glass transition temperature (T g ) of the composites, taken at the maximum value of the tan δ, is determined by the DMA [25,26]. As observed from Figure 5a, increasing the mass fraction of Fe 3 O 4 shifted the curve peak to low temperatures, with the incorporation of 1% Fe 3 O 4 into the PBMA matrix leading to the greatest decrease in T g , referring to neat PBMA.…”
Section: Resultsmentioning
confidence: 99%
“…The glass transition temperature (T g ) of the composites, taken at the maximum value of the tan δ, is determined by the DMA [25,26]. As observed from Figure 5a, increasing the mass fraction of Fe 3 O 4 shifted the curve peak to low temperatures, with the incorporation of 1% Fe 3 O 4 into the PBMA matrix leading to the greatest decrease in T g , referring to neat PBMA.…”
Section: Resultsmentioning
confidence: 99%
“…In order to measure the interlayer distance using the diffraction peak and its position in an XRD pattern, the Bragg's equation is typically employed [7] . Details of this equation have been explained by Rahman et al [11] .…”
Section: X-ray Diffraction Propertiesmentioning
confidence: 99%
“…A number of other researchers also began an investigations with various types of polymer nanocomposites [7][8][9] . Recently, it has been observed that by hybridising nanoparticles into the matrix of fibre-reinforced composites, synergistic effects may be achieved [10][11][12] . Mohan and Kanny [13] in their work, combined PP/NC composite with chopped GF.…”
Section: Introductionmentioning
confidence: 99%
“…In order to upgrade the properties of PP to match the profile of a typical engineering thermoplastic, proper fillers or reinforcements are incorporated into the PP matrix . Thus, composites of PP with a number of fillers have been prepared and studied in literature .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the silane modification of an organoclay on the properties of polypropylene/clay composites was further investigated by Joo et al Very good tensile properties were measured for the composites. Hybrid composites of PP with glass fiber and nanoclay were prepared by Rahman et al , and their microstructural, thermal, and mechanical properties were studied. It was found that the thermal stability of the material was improved and flexural strength and modulus were both enhanced.…”
Section: Introductionmentioning
confidence: 99%